Drosophila Insulin-Like Peptide 8 (DILP8) in Ovarian Follicle Cells Regulates Ovulation and Metabolism - Liao, Sifang; Nässel, Dick R. (Frontiers in Endocrinology, 2020)
In Drosophila eight insulin-like peptides (DILP1-8) are encoded on separate genes. These DILPs are characterized by unique spatial and temporal expression patterns during the lifecycle. Whereas functions of several of the DILPs have been extensively investigated at different developmental stages, the role of DILP8 signaling is primarily known from larvae and pupae where it couples organ growth and developmental transitions. In adult female flies, a study showed that a specific set of neurons that express the DILP8 receptor, Lgr3, is involved in regulation of reproductive behavior. Here, we further investigated the expression of dilp8/DILP8 and Lgr3 in adult female flies and the functional role of DILP8 signaling. The only site where we found both dilp8 expression and DILP8 immunolabeling was in follicle cells of mature ovaries. Lgr3 expression was detected in numerous neurons in the brain and ventral nerve cord, a small set of peripheral neurons innervating the abdominal heart, as well as in a set of follicle cells close to the oviduct. Ovulation was affected in dilp8 mutants as well as after dilp8-RNAi using dilp8 and follicle cell Gal4 drivers. More eggs were retained in the ovaries and fewer were laid, indicating that DILP8 is important for ovulation. Our data suggest that DILP8 signals locally to Lgr3 expressing follicle cells as well as systemically to Lgr3 expressing efferent neurons in abdominal ganglia that innervate oviduct muscle. Thus, DILP8 may act at two targets to regulate ovulation: follicle cell rupture and oviduct contractions. Furthermore, we could show that manipulations of dilp8 expression affect food intake and starvation resistance. Possibly this reflects a feedback signaling between ovaries and the CNS that ensures nutrients for ovary development. In summary, it seems that DILP8 signaling in regulation of reproduction is an ancient function, conserved in relaxin signaling in mammals.